The application of ecologically acceptable concept in liquid chromatographic method development in drug analyses - Otašević Biljana; Protić Ana; Golubović Jelena; Zečević Mira (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2015)
Liquid chromatography is the most widely used analytical technique in course of research and development, as well as for routine investigation and quality control of pharmaceutical products. Having in mind the remarkable amount of waist resulting from the use of organic solvents, especially for reversed-phase liquid chromatography, recently ecologically acceptable concepts in chromatographic method development were noticed. The 3 Rrule (Reduce - Replace - Recycle) refers to the decrease of the toxic solvents use, their replacement with less toxic ones and the use of renewable solvents. This paper presents different solutions commonly applied in drug analysis that are in accordance with the 3 Rrule.